Impact of Exercise Interventions on Elderly Heart Failure: Evaluating Aerobic, Resistance, and Combined Approaches - Ran Lifeng (International Journal of Education and Humanities, 2024)
In recent years, the number of elderly individuals has continued to rise, particularly in China, where aging has become a serious issue. Common symptoms of aging, such as hypertension, heart disease, and osteoporosis, are increasingly prevalent. Heart failure, a complication of heart disease, primarily affects the elderly and can severely impact their quality of life, even posing life-threatening risks. This study explores the impact of exercise interventions on the treatment and rehabilitation of heart failure in the elderly, aiming to provide more comprehensive and effective evidence. Keywords such as "exercise," "aerobic exercise," "resistance exercise," "combined exercise," "heart failure," and "elderly" were entered into databases like HowNet, Wanfang, VIP, PubMed, and Embased to select and summarize representative articles. The results indicate that all three types of exercise interventions positively affect elderly heart failure, though the degree of positive impact and improvement in related physical indicators vary. Targeted exercise interventions should be based on the type and severity of heart failure in the elderly. Aerobic exercise is recommended for patients with mild conditions, while resistance exercise is suitable for those with severe heart failure and muscle weakness. Combined exercise depends on concurrent symptoms, such as respiratory failure and the inability to stand. Further study is needed to better understand the relationship between exercise types and rehabilitation outcomes. Developing individualized intervention programs based on disease severity and overall physical condition is crucial. Additionally, educating and training healthcare professionals on implementing effective exercise intervention programs for elderly patients with heart failure is essential